Cultural Capital, Social Class and Higher Education: How Institutionalised Cultural Capital Shapes Educational Choice in Bangladesh - Nahar, Lata Lutfun (International Journal of Economics, Business and Management Studies, 2013)
The article examines the relationship between social class, cultural capital and undergraduate study in Bangladesh with an emphasis on institutionalised cultural capital, which is embedded within the class structure, and its role in determining choice of universities. The data for this study was collected from twenty four students from the University of Dhaka and the BRAC University, Bangladesh, employing observation and qualitative interview methods. The study finds that the medium of instruction (Bengali or English) in school makes a difference in the accumulation of institutionalised cultural capital and institutional habitus among the students of Bangladesh and their choice differ because of these factors. This study finds that students from Bengali medium schools choose mostly public universities, where the medium of instruction is mostly Bengali whereas students from the English medium and English version schools choose renowned universities abroad or renowned private universities in Bangladesh due to different institutionalised cultural capital and institutional habitus.